A novel cryptochrome in the diatom Phaeodactylum tricornutum influences the regulation of light‐harvesting protein levels. (7th April 2014) - Juhas, Matthias; von, Andrea; Spexard, Meike; Schmidt, Matthias; Kottke, Tilman; Büchel, Claudia
<x xml:space="preserve">Abstract</x> Diatoms possess several genes for proteins of the cryptochrome/photolyase family. A typical sequence for a plant cryptochrome was not found in our analysis of the Phaeodactylum tricornutum genome, but one protein grouped with higher plant and green algal cryptochromes. This protein, CryP, binds FAD and 5, 10‐methenyltetrahydrofolate, according to our spectroscopic studies on heterologously expressed protein. 5, 10‐Methenyltetrahydrofolate binding is a feature common to both cyclobutane pyrimidine dimer photolyases and DASH cryptochromes. In recombinant CryP, however, the FAD chromophore was present in its neutral radical state and had a red‐shifted absorption maximum at 637 nm, which is more characteristic for a DASH cryptochrome than a cyclobutane pyrimidine dimer photolyase. Upon illumination with blue light, the fully reduced state of FAD was formed in the presence of reductant. Expression of CryP was silenced by antisense approaches, and the resulting cell lines showed increased levels of proteins of light‐harvesting complexes, the Lhcf proteins, in vivo. In contrast, the levels of proteins active in light protection, the Lhcx proteins, were reduced. Thus, CryP cannot be directly grouped with known members of the cryptochrome/photolyase family. Of all P. tricornutum proteins, it is the most similar in sequence to a plant cryptochrome, and is involved in the regulation of light‐harvesting protein expression, but shows spectroscopic features and a chromophore composition that are most typical of a DASH cryptochrome.